Régiók nélküli regionalizmus Magyarországon - Bajor, Tibor (Közép-Európai Közlemények, 2016)
Hungary historical – administrative structure does not recognize the separation of powers system. The role, mission for the creation, and necessity of the region, since the beginning of the EU accession process, the subject of debate in the Hungarian regional development public life. Not for himself – in a matter of establishment in the region – opposed (this is more – or less everyone took note until 2011), but the fact that after the formation regions, how it will operate in the region and what will be the with counties? So elected political and administrative regions after formation: what should be the role of the county and region, administratively and politically? The Regional Development Act (the subject called basic law) law was passed practically this problem „swept under the table!” Following the European Union’s accession to the EU concept development and organizational systems „Hungarian style” appeared in public administration. In my paper this political and historical reasons to want analyzed.